Teachers' Perceptions of the Use of Canva in Developing Islamic Religious Education Learning at MTS Muhammadiyah 7 Panceng - Al-Muzzaki, Rizqi Hariyono; Bakhruddin, Muhammad; Puspitasari, Ika (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This research aims to analyze teachers' perceptions of the use of Canva in PAI learning development at MTS Muhammadiyah 7 Panceng. The research method used is a qualitative approach with data collection techniques through interviews, observations, and observations. The research subjects included students and PAI teachers at MTS Muhammadiyah 7 Panceng. The results showed that PAI teachers at MTS Muhammadiyah 7 Panceng school considered Canva as an effective learning tool in improving the quality of PAI learning materials, because of the various templates and interesting features provided by Canva from free to paid. The use of Canva helps teachers in creating interactive and interesting learning materials, thus increasing students' interest and motivation to learn. However, some teachers experience technical difficulties and need optimal training in using Canva. This research contributes to the development of innovative and effective PAI learning strategies. The results of this study can be used as a reference for PAI teachers in developing quality learning materials.